(untitled) (CIPEEX, 2025)
This document outlines the development of a comprehensive cash register system designed for effective restaurant management. The primary objective of this system is to streamline operations by integrating functionalities such as sales registration, inventory management, employee tracking, financial reporting, payment processing, and order control into a unified platform. The method involves implementing a user-friendly interface that facilitates ease of use for restaurant staff while ensuring accurate and real-time data handling. Key features include tracking menu items, quantities, and prices during sales, updating inventory based on sales activity, recording employee work hours, generating detailed financial reports, and integrating various payment methods including cash and cards. The system also monitors the status of orders from placement to delivery. Results demonstrate improved operational efficiency and enhanced financial oversight, leading to better management and resource allocation. Conclusions indicate that this system effectively supports the restaurant’s daily operations, offering a robust solution for managing complex tasks and improving overall performance.